Odpowiedzialność społeczna w działalności edukacyjnej - Pisz, Zdzisław (Social Responsibility in Educational Activity, 2009)
The article presents a view of business social responsibility in the context of social tasks. The main aspect of the article concentrates on schools which operate in a "social way" and in a "business way" as well. The author shows similarities and differences between corporate social responsibility and social responsibility of schools. At the same time he points a lot of aspects and questions which need future research.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 61-71